Odpowiedzi

2010-02-08T17:17:13+01:00
2x-1=4x+2
-2x=3 / :(-2)
x=-1,5

¼x+2=-4+⅓x / *12
3x+24=48+4x
-x=24 / :(-1)
x=-24

4x-3(x+7)-5x=-2(x-1)+9
4x-3x-21-5x=-2x+2+9
-4x-21=-2x+11
-2x=32 / :(-2)
x=-16
  • Użytkownik Zadane
2010-02-08T17:20:55+01:00
2x-1=4x+2 /-4x
-2x-1=2 /+1
-2x=3 /:(-2)
x=-3/2=-1 ½

¼x+2=-4+⅓x
3/12x + 2= -4+ 4/12x /-4/12x
-1/12x+2=-4
-1/12x=2 /:(-1/12)
x=1/6

4x-3(x+7)-5x=-2(x-1)+9
4x-3x-21-5x=-2x+2+9
-4x-21=-2x+11
-2x-21=11
-2x=32
x=-16
2010-02-08T17:26:44+01:00
2x-1=4x+2
2x-4x=2+1
-2x=3|/(-2)
x=3/-2
x=-1.5

(1/4x)+2=-4+(1/2x)
(1/4x)+(-1/2x)=-4-2
3/2x-1/2x=-6
x=-6

4x-3(x+7)-5x=-2(x-1)+9
4x-3x-21-5x=-2x+2+9
4x-3x+2x-5x=2+9+21
-2x=32|/(-2)
x=-16